Identificação e mapeamento de regiões potenciais à instalação de turbinas hidrocinéticas na bacia hidrográfica do Rio São Francisco Verdadeiro – Oeste do Paraná - Amaral, Camila Zeni do (2021)
Environmental issues are the biggest factor in the search for cleaner energy production alternatives. The use of hydrokinetic turbines can be a viable option for communities close to rivers that have specific hydrological characteristics. Using geoprocessing techniques, it was identified and mapped within the São Francisco Verdadeiro River Basin (SFV), potential sites for installing hydrokinetic systems to generate electricity. Digital Alos Palsar Elevation Models chosen by the NASA EarthData project and images from Landsat 8 (L8) were used. Thematic mapping and subsequent analysis of sites with hydrokinetic potential in the study unit were carried out. 10 points with known flow along the SFV river in the dry period were selected, from which the basic parameters were obtained for calculating the water velocity using the Chezy equation. The required rotor diameter for each point was calculated at the maximum depth of the section as well as the available hydrokinetic potential at each point, considering the minimum (Cp = 0.25) and the maximum (Cp = 0.593) efficiency of a turbine, thus the energy production capacity was calculated at each point. Based on theoretical data collection, it was found that there is no hydrokinetic potential available in the studied points of the São Francisco Verdadeiro River.